A Study on Religious Values in Harun Yahya’s Fable - Irmawaty Hasyim; Salmia Syarifuddin (Fakultas Sastra - Universitas Muslim Indonesia, 2019)
This study purposes to describe the religious values in Harun Yahya’s fables. This study used the descriptive qualitative method. The data source of this research was fable by Harun Yahya such as; Omar and the Penguin, Jamal and the Parrot, and Naeem and the Pretty Peacock. The data in this study could be a phrase, be it a noun phrase or verb, sentences and discourse fragment found in the fable. Data collection and analysis techniques used was content analysis techniques. The results showed that the religious value of character education appeared in the fables gave pieces of advice to the readers about getting closer to God Allah SWT.